UPAYA NINIAK MAMAK KAUM MENANGGULANGI KENAKALAN ANAK KEMANAKAN DI JORONG II KOTO PANJANG NAGARI LANSAT KADAP KEC. RAO SELATAN - Adilman Adilman; Muhiddinur Kamal (Universitas Pahlawan Tuanku Tambusai, 2022)
The background of the author raised this title Where in this jorong teenagers behave negatively which is far from the demands of the teachings of Islam, this behavior can be seen from their daily behavior such as preferring to sit on the side of the road while playing guitar, drinking and gambling. The purpose of this study was to determine the efforts made by Ninik Mamak to overcome juvenile delinquency in Jorong II Koto Panjang. This research method is descriptive qualitative, the informants consist of key informants and supporting informants, the key informants in this research are Ninik mamak jorong II kotopanjang, the supporting informants in this study are jorong II kotopanjang adolescents. The research here uses research instruments in the form of interviews and observations. The results of this study indicate that Ninik Mamak has carried out her efforts in fostering the morals of her nephews in Jorong II Koto Panjang. However, the efforts made by ninik mamak are still not maximized, such as the need for further improvements to kinship, such as holding meetings to study customs, religion, and government with nieces and nephews, educating to become traditional heirs. Because there are still ninik mamak who have not played their role. For the perfection of efforts to carry out the duties and obligations of caring for nephew's children, ninik mamak have main tasks including, Knowing the number of clan members in this case Ninik mamak must know in detail about the number of clan members. Based on the interviews and observations the author did, all of the ninik mamak's obligations gave the same answer, namely: Participate in thinking and solving problems and difficulties faced by the nephew's children. Whatever the problem, the mamak niece takes part in solving and ordering to do good and stay away from the prohibitions regulated by religion, custom and the government. A ninik mamak must pay attention to his nephew in his daily life in behavior. Ninik mamak ordered her niece to do good and stay away from prohibitions in accordance with religion, custom and government. The number of nieces and nephews of ninik mamak people in Jorong II Koto Panjang there are 36 teenagers including 21 boys and 15 girls, while there are 25 people who have problems. Efforts made by ninik mamak are to visit the children's nephew's house to give advice in the form of how to get along, dress politely and with good manners. Keywords: ninik mamak people, nephew's child delinquency.